An Extensive Review on Production, Purification, and Bioactive Application of Different Classes of Bacteriocin - Manovina Manoharan; Thamarai Selvi Balasubramaniam (Journal of Tropical Biodiversity and Biotechnology, 2022)
Lactic Acid Bacteria (LAB) synthesize various metabolites during their growth phase and are Generally Recognized as Safe (GRAS) and Qualified Presumption of Safety (QPS). Ribosomally synthesized Antimicrobial Peptides (AMP) or Bacteriocins from the genera of Lactic Acid Bacteria and other prokaryotic genera are cationic, heat-stable, amphiphilic and the membrane permeabilizing peptides built with an excess amount of lysyl and arginyl residues. Antimicrobial compounds produced by LAB depend on the physical and biological conditions of microbial culture. Different classes of bacteriocin are produced by both Gram-positive and Gram-negative bacteria. The production of bacteriocin is influenced by various environmental factors. Bacteriocin has a wide variety of applications in various fields.   The application spectrum of bacteriocins can be expanded in various domains such as food processing, biomedical, and personal care due to the increase in the number of newly discovered bacteriocins. Bacteriocins acquire a wide spectrum of antimicrobial activity with minimal level of cytotoxicity. In addition, bacteriocins were studied for their anticancer activity against different cancer cell lines. Selective binding of bacteriocins (cationic) towards cancer cells (anionic) increases the cytotoxicity of cancer cells. Bacteriocin peptides initiate necrosis by communicating with the cell surface which selectively targets and kills the cells with tumor formation and does not cause any damage to the normal healthy cells. In this review, the bacteriocins synthesized from lactic acid bacteria along with their interaction with cancer cell lines and other applications are discussed along with a few examples of other bioactive compounds produced by LAB.